(untitled) (Global Journal of Science Frontier Research, 2020)
Using plasma equations beside Maxwell statistical distribution law a useful expression of the Neel temperature similar to that obtained for high temperature superconductors was derived. This expression was found by obtaining a new expression of energy from the plasma equation. The same procedures were used to find an expression of the pressure and isotope mass in terms of the critical temperature for high temperature superconductors. These expressions resembles the conventional ones.